Modulation of excitatory neurotransmission by neuronal/glial signalling molecules: interplay between purinergic and glutamatergic systems - Köles, László (Purinergic Signal, 2015)
Glutamate is the main excitatory neurotransmitter of the central nervous system (CNS), released both from neurons and glial cells. Acting via ionotropic (NMDA, AMPA, kainate) and metabotropic glutamate receptors, it is critically involved in essential regulatory functions. Disturbances of glutamatergic neurotransmission can be detected in cognitive and neurodegenerative disorders. This paper summarizes the present knowledge on the modulation of glutamate-mediated responses in the CNS. Emphasis will be put on NMDA receptor channels, which are essential executive and integrative elements of the glutamatergic system. This receptor is crucial for proper functioning of neuronal circuits; its hypofunction or overactivation can result in neuronal disturbances and neurotoxicity. Somewhat surprisingly, NMDA receptors are not widely targeted by pharmacotherapy in clinics; their robust activation or inhibition seems to be desirable only in exceptional cases. However, their fine-tuning might provide a promising manipulation to optimize the activity of the glutamatergic system and to restore proper CNS function. This orchestration utilizes several neuromodulators. Besides the classical ones such as dopamine, novel candidates emerged in the last two decades. The purinergic system is a promising possibility to optimize the activity of the glutamatergic system. It exerts not only direct and indirect influences on NMDA receptors but, by modulating glutamatergic transmission, also plays an important role in glia-neuron communication. These purinergic functions will be illustrated mostly by depicting the modulatory role of the purinergic system on glutamatergic transmission in the prefrontal cortex, a CNS area important for attention, memory and learning.